Elemento (III) Derivatives of N-(2-Hydroxy-3-Methyl Benzyl) Alanine - Kandpal, Munju; Chandra, Madhup (Asian Journal of Chemistry, 2010)
Several elemento(III) viz. boron, aluminium, iron, arsenic and antimony derivatives of N-(2-hydroxy-3-methyl benzyl) alanine have been prepared by the interaction of the corresponding elemento (III) isopropoxide with the latter in 1 : 1, 1 : 2 and 1 : 3 molar ratios in benzene medium. The compounds thus prepared were generally obtained as coloured solids, with some of them being hygroscopic. All these compounds have been characterized by azeotrope and elemental analyses, as well as by IR and PMR spectral measurements.